2023
DOI: 10.1002/ajh.26799
|View full text |Cite
|
Sign up to set email alerts
|

Clinico‐genetic and prognostic analyses of 716 patients with primary myelodysplastic syndrome and myelodysplastic syndrome/acute myeloid leukemia based on the 2022 International Consensus Classification

Abstract: The 2022 International Consensus Classification (ICC) recategorized myeloid neoplasms based on recent advances in the understanding of the biology of hematologic malignancies, in which myelodysplastic syndrome (MDS) with blasts of 10%-19% is classified as MDS/acute myeloid leukemia (AML), MDS with mutated SF3B1, irrespective of the number of ring sideroblasts, as MDS-SF3B1, and those with multi-hit TP53 mutations as MDS with mutated TP53. In the analysis of 716 patients with MDS diagnosed according to the 2016… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…S1A ). This is in line with a previous study by Lee et al analyzing 173 MDS/AML patients that additionally found OS differences between MR subgroups [ 11 ]. As expected, MDS/AML patients were mainly composed of MDS-IB2 (114/137; 83%) according to WHO 2022.…”
Section: To the Editorsupporting
confidence: 93%
“…S1A ). This is in line with a previous study by Lee et al analyzing 173 MDS/AML patients that additionally found OS differences between MR subgroups [ 11 ]. As expected, MDS/AML patients were mainly composed of MDS-IB2 (114/137; 83%) according to WHO 2022.…”
Section: To the Editorsupporting
confidence: 93%
“…Patients diagnosed with MDS/AML had higher risk features than those diagnosed with MDS (Supplementary Table 3 ). Most patients with MDS or MDS/AML with mutated TP53 had very high-risk IPSS-M/R or high-risk IPSS, as described previously [ 26 ] (Supplementary Tables 4 and 5 ). Patients at higher-risk IPSS-M received disease-modifying treatments (hypomethylating agent [HMA], intensive chemotherapy, clinical trials, or HSCT) more frequently than those with lower-risk IPSS-M (46.5% vs. 17.6%, P < 0.001; Supplementary Table 2 ).…”
Section: Resultsmentioning
confidence: 85%
“…According to a recent study [ 26 ] that explored the clinico-genetic features and prognostic implication of the 2022 ICC, the MDS-del(5q), MDS- SF3B1 , and MDS, NOS with SLD/MLD were defined as low-risk MDS. In the univariable analysis, bedside IPSS-M, IPSS-R, IPSS, older age, male sex, and ferritin level were associated with poorer outcomes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While SLD and MLD distinction remains in MDS, NOS subclassification in the ICC is optional in WHO-2022 criteria. Considering the heterogeneous results from previous studies [ 25 , 26 ], we believe that further analysis is warranted to assess the survival impact of the lineage of dysplasia. Our study also revealed distinct features in patients with MDS- SF3B1 compared to those with MDS-LB and RS, and MDS-LB, the latter two subtypes showing similar mutational landscapes.…”
Section: Discussionmentioning
confidence: 99%